Review of the cardinalfishes of the genus Cercamia (Percomorpha: Apogonidae) of the Red Sea and Indian Ocean with descriptions of three new species - Fraser, Thomas H.; Bogorodsky, Sergey V.; Mal, Ahmad O.; Alpermann, Tilman J. (Zootaxa, 2021)
The representatives of Cercamia from the Indian Ocean including Red Sea are reviewed and three new species are described: Cercamia spio n. sp., formerly known as C. eremia (Allen, 1987), is described from 14 specimens, 17–33 mm SL, collected in 10–15 meters from northern (Duba) to central (Jeddah) Saudi Arabia and from Jezirat Fara’un, Egypt. It also has been photographed from the Gulf of Aqaba (Dahab, Egypt) and El Quseir (Mangrove Bay, Egypt). The new species is distinguished from other Indian Ocean Cercamia in having fewer developed gill rakers on lower limb (usually 11 versus usually 12–13) and fewer anal-fin rays (11 versus usually 12–13). Another new species, Cercamia laamu, n. sp., is described only from the Maldives and Chagos Archipelago based on five specimens 16.0–30.5 mm SL. It differs from all Indian Ocean Cercamia in having more greater number of the second dorsal-fin rays (10 versus usually 9), and a translucent body devoid of reddish marks versus small reddish dots and crisscross lines. The third new species, Cercamia mascarene, n. sp., is described from 40 specimens 19–36 mm SL, from Rodrigues Island, Mauritius. It differs from Cercamia eremia in having a greater number of developed gill rakers on the lower limb of the first gill arch (usually 13 versus usually 12). Free neuromasts and cephalic pores are illustrated for Cercamia mascarene and free neuromasts on the body and caudal fin are illustrated for Japanese specimens of C. cf. eremia. New diagnoses are provided for Cercamia cladara, the type species of the genus, and C. eremia. A map of collection locations for species of Cercamia is presented to show the breath of known occurrences in the Red Sea and Indian Ocean. A new morphologic diagnosis is provided for Cercamia. A phylogenetic analysis of the barcoding portion of the mitochondrial COI gene, including all available sequences from members of the genus Cercamia, displays a much higher species diversity than expected, with high levels of divergence among recognized and undescribed species. A key to the described Indian Ocean species is provided.